International ENTER Project: A New Pedagogical Training Approach for Engineering Educators - F. T. Shageeva; E. S. Mishchenko; N. G. Chernyshov; K. E. Nurgalieva; K. M. Turekhanova; Y. T. Omirzhanov (Moscow Polytechnic University, 2020)
The formation of a modern generation of engineers capable to drive changes that meet the requirements of the future necessitates a new approach in pedagogical training of engineering teachers. The international ENTER (EngineeriNg educaTors pEdagogical tRaining) project is being developed as part of EU Erasmus program focused on addressing the actual education needs from the standpoint of human and social capitals development both in Europe and in other countries. The ENTER project is aimed at the creation and development of an international platform for multilevel vocational training/retraining of technical universities teachers on the basis of the Eurasian interaction network. Surveys among employers, teachers, and engineering university students, as well as scientific periodicals analysis allowed us to determine the complex of universal and specific engineering and pedagogical competencies that educators should master not only for today, but also for the future needs. Based on the competency analysis, a three-level modular teacher training/retraining program (iPET program) has been developed and its international accreditation is planned.